EKSISTENSI HUKUM ADAT ENDE LIO DALAM KASUS PERKAWINAN “PARU DHEKO” (KAWIN LARI) PADA MASYARAKAT KELURAHAN BOKASAPE KECAMATAN WOLOWARU KABUPATEN ENDE - Eka Hilda Sangraini; Antonius M. K. Naro; Yanto Yanto (Ensiklopedia of Journal, 2026)
This study discusses the role of Ende Lio customary law in resolving cases of Paru Dheko (elopement) Marriage in Bokasape Village, Wolowaru Subdistrict, and Ende Regency. The background of this research stems from concerns about the deviation of marriage practices from the prevailing customary rules. Paru Dheko occurs without family consent and without going through customary stages, and is therefore viewed as a violation of traditional norms. The study employs a qualitative method with an ethnographic approach, conducted through in-depth interviews with elopement actors, traditional leaders, and community members. The findings indicate that Paru Dheko is triggered by factors such as parental disapproval, premarital pregnancy, differences in social status, and economic limitations. Although the process does not follow customary procedures, the resolution is still carried out through customary means with mediation by traditional leaders (Mosalaki), particularly in determining the belis (dowry) and marriage arrangements. Customary law remains the main guideline for maintaining harmony, resolving conflicts, and preserving the cultural values of the Ende Lio community.  Keywords: Marriage; Paru Dheko; Customary Law